Les « cinébus » dans la tourmente - Sébastien Denis (Revue des Mondes Musulmans et de la Méditerranée)
This article presents the work of the Movie Distribution Service (abbreviated as SDC in French) of the General Government of Algeria, a propaganda effort based on showing films on colonial Algeria to rural populations in the country. Single-handed at first from 1945 onward, the SDC was helped by the army during the Algerian war and initiated a psychological warfare to spread a positive image of France and the Algerian administration. Following the massacres in Sétif, in a tense political context leading to the call to order of independence movements, it was a way to offer an ideal vision of the relations between France and Algeria. Staffed mainly with Europeans living in Algeria, the service reflected, through detailed reports, both the rise of latent anti-colonialism in public opinion and the officials’ faith in French Algeria.